An initial approach to the impact of roller screen curtains on colour rendition of transmitted daylight: Experimental measures in real space - Villalba, Ayelén María (2023)
Several studies on roller screen shades performance have been conducted focusing on glare, outdoor vision, daylight availability and energy performance. However, other properties—such as chromaticity and colour rendition—of daylight transmitted through this type of shading system have hardly been addressed. Against this background, the present study focuses on the impact of woven shade fabrics on daylight conditions in indoor spaces, targeting variations in colour rendition properties. The hypothesis of this work is that the fibre colour and the openness factor of woven shade fabrics, as well as, the solar incidence position affect the colour rendition properties of the transmitted daylight. Seven screen fabrics were evaluated in a test room, where the CRI and the spectral power distribution (SPD) were measured, at two distinct times of the day. Based on the SPD the Fidelity Index, the Gamut Index and the red Local Chroma Shift were calculated. Results show that the daylight passing through the fabrics has good or excellent colour rendition capacity for the tested samples and the testing conditions. And that the solar position impacts on the studied colour rendition metrics, whereas the openness factor and the colour of the fabric do not.